Epidemiological profile of hospitalizations for obesity in Brazil, in the period from 2017 to 2021 (Research, Society and Development, 2022)
The objective was to trace the profile of hospitalizations for obesity in Brazil from 2017 to 2021. This is an observational, descriptive and quantitative study. The data are for the period from january 2017 to september 2021, collected from the SUS Hospital Morbidity Information System. The research sample addresses individuals according to age group, gender and race, who suffered hospitalizations or died due to obesity in hospitals in the country during this time interval. In relation to thenumber of hospitalizations, the South Region was responsible for 53.69%, while the North Region presented 0.64%. When the age of the individuals was observed, the predominant age group was between 30 and 39 years old, representing 33.20% of the hospitalizations, while children and adolescents up to 19 years old occupied only 0.97%. Women stood out with 86.54% of the hospitalizations, while men accounted for only 13.46%. Considering color/race, whites accounted for 63.37%, while Indians and yellow people totaled 0.74%. The national average mortality rate for obesity was 0.20/100,000 inhabitants, with the highest value in 2020, in the age group of 80 years or older. It was observed that the highest number of hospitalizations for obesity in Brazil is related to the South Region, predominantly in women over 40 years, with proportional growth according to increasing age and preferentially in white individuals. The mortality rate is more associated with the elderly aged 80 years or more.